Issues and prospects of image‐guided thermal ablation in the treatment of primary and metastatic lung tumors - Wang, Meixiang; Wei, Zhigang; Ye, Xin (Thoracic cancer, 2023)
The precise local minimally invasive or noninvasive treatment represents the important orientation for advancing the treatment of pulmonary malignant tumors. New local treatment methods have emerged as solutions to the shortcomings of minimally invasive or local treatment methods. Image‐guided thermal ablation (IGTA) comes with the characteristics such as more accurate localization, less trauma, more definite efficacy, higher safety, stronger repeatability, fewer complications, and lower cost in treating lung tumors. This paper investigates the existing problems of IGTA in the treatment of lung tumors and puts forward the orientation of studies.